Burden, causes, and outcomes of people with epilepsy admitted to a rural hospital in Kenya. (16th February 2015) - Kariuki, Symon M.; Chengo, Eddie; Ibinda, Fredrick; Odhiambo, Rachael; Etyang, Anthony; Ngugi, Anthony K.; Newton, Charles R. J. C.
Summary Objective People with epilepsy (PWE) develop complications and comorbidities often requiring admission to hospital, which adds to the burden on the health system, particularly in low‐income countries. We determined the incidence, disability‐adjusted life years (DALYs), risk factors, and causes of admissions in PWE. We also examined the predictors of prolonged hospital stay and death using data from linked clinical and demographic surveillance system. Methods We studied children and adults admitted to a Kenyan rural hospital, between January 2003 and December 2011, with a diagnosis of epilepsy. Poisson regression was used to compute incidence and rate ratios, logistic regression to determine associated factors, and the DALY package of the R‐statistical software to calculate years lived with disability (YLD) and years of life lost (YLL). Results The overall incidence of admissions was 45.6/100, 000 person‐years of observation (PYO) (95% confidence interval [95% CI] 43.0–48.7) and decreased with age (p < 0.001). The overall DALYs were 3.1/1, 000 (95% CI, 1.8–4.7) PYO and comprised 55% of YLD. Factors associated with hospitalization were use of antiepileptic drugs (AEDs) (odds ratio [OR] 5.36, 95% CI 2.64–10.90), previous admission (OR 11.65, 95% CI 2.65–51.17), acute encephalopathy (OR 2.12, 95% CI 1.07–4.22), and adverse perinatal events (OR 2.87, 95% CI 1.06–7.74). Important causes of admission were epilepsy‐related complications: convulsive status epilepticus (CSE) (38%), and postictal coma (12%). Age was independently associated with prolonged hospital stay (OR 1.02, 95% CI 1.00–1.04) and mortality (OR, 1.07, 95% CI 1.04–1.10). Significance Epilepsy is associated with significant number of admissions to hospital, considerable duration of admission, and mortality. Improved supply of AEDs in the community, early initiation of treatment, and adherence would reduce hospitalization of PWE and thus the burden of epilepsy on the health system.